2022
DOI: 10.3390/cancers14236007
|View full text |Cite
|
Sign up to set email alerts
|

The Reporting, Use, and Validity of Patient-Reported Outcomes in Multiple Myeloma in Clinical Trials: A Systematic Literature Review

Abstract: Background: Patient-reported outcomes (PROs) are becoming increasingly important in supporting clinical outcomes in clinical trials. In multiple myeloma (MM), PRO measurement is useful to reveal how treatment affects physical, psychosocial, and functional behaviour as well as symptoms and treatment-related adverse events to evaluate the benefit-risk ratio of a particular drug or drug combination. We report the types of PRO instruments used in MM, the frequency in which they are utilised in randomised controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 35 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…In MM, as for many diseases, PROs have become an increasingly important tool to support clinical outcomes, and help guide clinicians towards tailoring treatment to their patients' needs and lifestyles. 15,16 The EASEMENT study aimed to determine satisfaction with, and preference of, the treatment received, treatment patterns, and resource use, stratified by both route of administration (orals vs. injectables) and MM status in patients who had received ≥1 cycle of their current line of therapy at the index date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MM, as for many diseases, PROs have become an increasingly important tool to support clinical outcomes, and help guide clinicians towards tailoring treatment to their patients' needs and lifestyles. 15,16 The EASEMENT study aimed to determine satisfaction with, and preference of, the treatment received, treatment patterns, and resource use, stratified by both route of administration (orals vs. injectables) and MM status in patients who had received ≥1 cycle of their current line of therapy at the index date.…”
Section: Discussionmentioning
confidence: 99%
“…1,12 While oral therapies offer the potential for greater convenience versus conventional injectable regimens, 13,14 data on patient-reported outcomes (PROs) such as patient preferences, QoL, and healthcare utilisation, have only recently started to be reported. [15][16][17][18][19][20] Receiving injectable treatment usually requires hospital visits and administration by a healthcare provider 16 ; several recent studies identified oral medication as an important factor for patients with MM, based on greater perceived treatment convenience, less impairment of daily activities and work productivity. [16][17][18][19][20] However, there are limited data about patient perspectives, experiences, and expectations of their MM treatment 21 or when patients switch from injectable to oral therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Bone lesions, bone marrow and renal failure, and immunodeficiency contribute to many complications of the disease. 4 Advances in anti-myeloma treatments have improved disease response rates and patient life expectancy; however, they are accompanied by multiple side effects, most commonly infections and neurological, haematopoietic and cardiac toxicities, which can impact patient QOL. [4][5][6][7] Moreover, health-related QOL deteriorates with each subsequent relapse and line of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4 Advances in anti-myeloma treatments have improved disease response rates and patient life expectancy; however, they are accompanied by multiple side effects, most commonly infections and neurological, haematopoietic and cardiac toxicities, which can impact patient QOL. [4][5][6][7] Moreover, health-related QOL deteriorates with each subsequent relapse and line of therapy. 5 Thus, treatment goals for patients with relapsed or refractory multiple myeloma (RRMM) should also include managing disease and treatmentrelated symptoms to maintain or potentially improve their QOL in addition to extending their survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation